ENGAGING THE ADULT ELS: AN IN-DEPTH ANALYSIS OF GAMIFICATION’S IMPACT OM MOTIVATION AND LEARNING EFFICACY IN BEGINNER ELS GRAMMAR CLASSROOM - Noor , Laila (UICELL, 2023)
This study investigates the impact of gamification on motivation, engagement, and assessment anxiety among adult learners in an ESL grammar classroom. With the increasing adoption of digital learning tools, understanding their effects on adult learners, especially in language acquisition, is crucial. Participants in this study were adult learners at a beginner English proficiency level, who engaged in a grammar assessment through the Kahoot platform. The assessment included various grammar tasks designed to evaluate comprehension and retention. Employing thematic analysis of the data revealed significant findings: gamification led to improved motivation and engagement, enhanced visual learning, decreased test anxiety, and heightened enjoyment. These outcomes suggest that integrating gamification into ESL grammar teaching can create a more dynamic and inclusive learning environment, catering to diverse learning styles. The research underscores the potential of gamification not just in teaching, but also in evaluating student comprehension effectively. The study calls for further studies to explore the long-term impacts of gamification and its applicability across different stages of ESL learning. Keywords: ESL grammar, Adult learning, gamification, motivation, test anxiety